2005
DOI: 10.1073/pnas.0502320102
|View full text |Cite
|
Sign up to set email alerts
|

The Sca-1 cell surface marker enriches for a prostate-regenerating cell subpopulation that can initiate prostate tumorigenesis

Abstract: The prostate contains classes of epithelial cells with variable differentiation status that may serve as targets for tumor initiation (8-10). Androgen cycling experiments suggest that stem cell activity is present in the prostate (11). These cells are thought to reside in the basal layer of the prostate because these cells are androgen-independent and preferentially retained in castrated rodents. Stem cells in the basal layer give rise to transit-amplifying epithelial cells (TACs) that differentiate to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
402
0
7

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(422 citation statements)
references
References 34 publications
10
402
0
7
Order By: Relevance
“…Moreover, Wu et al recently demonstrated a tumor suppressive function of MAP3K7/TAK1 in a shTAK1 prostate cancer mouse model system. 6,31 Also considering the biological role of MAP3K7 as a regulator of cell growth, differentiation and apoptosis, 7-9 the evidence for MAP3K7 representing the relevant tumor suppressor gene on 6q15 is very strong.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wu et al recently demonstrated a tumor suppressive function of MAP3K7/TAK1 in a shTAK1 prostate cancer mouse model system. 6,31 Also considering the biological role of MAP3K7 as a regulator of cell growth, differentiation and apoptosis, 7-9 the evidence for MAP3K7 representing the relevant tumor suppressor gene on 6q15 is very strong.…”
Section: Discussionmentioning
confidence: 99%
“…These and more recent findings (Hope et al, 2004) strongly suggest that leukemic cells exist in a hierarchical state in which only a small number of cells are able to self-renew extensively, and thus capable of initiating and maintaining the leukemic clone. This hierarchical model of leukemia in which a rare stem cell initiates and maintains disease has since been extended to a range of other tumors including multiple myeloma (Matsui et al, 2004), mammary carcinomas (Ponti et al, 2005), colon cancer (O'Brien et al, 2007), prostate cancer (Xin et al, 2005) and brain tumors (Singh et al, 2004). Such findings raise great interest in both the target cells that can give origin to LSCs and the mechanisms underlying their key properties such as self-renewal.…”
Section: Hox and The Leukemic Stem Cellmentioning
confidence: 99%
“…Mixing experiments produce only monochromatic tubules, suggesting that they are also clonally derived (Azuma et al 2005;Xin et al 2005). IHC analysis of these prostatic grafts reveals both CK5-positive basal cells in the outer layer of most tubules and CK8-positive luminal cells in the inner regions (Fig.…”
Section: In Vitro Colony-forming Unit Assaymentioning
confidence: 99%
“…Since then, populations enriched for stem cell activity have been isolated from many adult tissues using various magnetic bead and FACS techniques Stingl et al 2006;Corti et al 2007). We and other investigators first identified the glycosyl phosphatidylinositol-anchored cell surface protein Sca-1 as a marker that can enrich for prostate stem cell activity, using magnetic bead sorting methods combined with in vitro and in vivo readout assays (Burger et al 2005;Xin et al 2005). …”
Section: Isolationmentioning
confidence: 99%